2005
DOI: 10.17221/3623-pse
|View full text |Cite
|
Sign up to set email alerts
|

Benzothiazole derivatives substituted in position 2 as biologically active substances with plant growth regulation activity

Abstract: Thirteen of the new synthetized 2-R substituted benzothiazole derivatives have been tested for plant growth regulatory (PGR) activity. The effect on growth elongation was studied on wheat coleoptile segments Triticum aestivum L. cv. Blava, and on the hypocotyl and roots in cucumber Cucumis sativum L. cv. Evita. The formation and number of adventitious roots and the length of hypocotyl in Vigna radiata (L.) Wilczek and, the effect on the length of stem, fresh and dry mass in buckwheat Fagopyrum esculen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…Similar studies were conducted in a work [85] that showed that synthetic 2-R substitutedbenzothiazole derivatives demonstrated dominant auxine-like plant growth promoting activity.Based on obtained results, showing that the plant growth promoting activity of synthetic benzothiazole compounds can be correlated with the activity of IAA synthetase, the authors have proposed that the mode of action ofsynthetic 2-R substitutedbenzothiazole derivatives as auxine-like substances is due to their possible regulation of synthesis or degradation of endogenous auxin indole-3-acetic acid (IAA) in plants.…”
Section: Regulating Activity Of Synthetic Lmwhc and Auxins Iaa And Nasupporting
confidence: 65%
See 1 more Smart Citation
“…Similar studies were conducted in a work [85] that showed that synthetic 2-R substitutedbenzothiazole derivatives demonstrated dominant auxine-like plant growth promoting activity.Based on obtained results, showing that the plant growth promoting activity of synthetic benzothiazole compounds can be correlated with the activity of IAA synthetase, the authors have proposed that the mode of action ofsynthetic 2-R substitutedbenzothiazole derivatives as auxine-like substances is due to their possible regulation of synthesis or degradation of endogenous auxin indole-3-acetic acid (IAA) in plants.…”
Section: Regulating Activity Of Synthetic Lmwhc and Auxins Iaa And Nasupporting
confidence: 65%
“…The assumptions discussed in the works [82][83][84][85] are consonant with our early published work [86], which testified in favor of theindirect, mediated through endogenous phytohormonesaction of synthetic LMWHC, derivatives of pyridinelutidine N-oxide (Ivin) and pyrimidine -6-methylthiouracil(Methyur)on plant cell extension, and published works of other authors [87 -92]thatshowed the effect of exogenously applied synthetic multi-dimensional plant growth regulator Thidiazuron (TDZ; N-phenyl-1,2,3-thidiazole-5ylurea) on increase in concentrations of endogenous cytokinins, auxin, ethylene and ABA in plant cells.…”
Section: Regulating Activity Of Synthetic Lmwhc and Auxins Iaa And Namentioning
confidence: 99%
“…As is known, the major plant hormones auxins are involved in control of plant embryogenesis, seed germination, cell elongation and division in plant hypocotyls and coleoptiles, apical dominance, cambium cell division, plant tropisms, growth and development of root system, promotion of fruit setting, prevention of leaf abscission, plant-pathogen interactions, and in vitro morphogenesis in plants [30][31][32][33][34][35][36][37][38][39][40][41] .…”
Section: Bioassay On Auxin-like Activity Of Chemical Low Molecular Wementioning
confidence: 99%
“…The most well-known bioassays include bioassays specific for auxin-like and cytokinin-like activities based on a stimulating effect of natural or chemical compounds on the basic processes of plant growth such as acceleration of the germination of plant seeds and growth of plant seedlings, elongation of hypocotyl or coleoptile on the plant seedlings, formation of the adventitious roots on the plant seedlings or on the isolated stem and leaf cuttings, increasing of growth of biomass of cotyledons isolated from plant seeds, delaying of leaf senescence, and in vitro morphogenesis in plants [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] .…”
Section: Introductionmentioning
confidence: 99%
“…2 2-Aminobenzothiazoles can be obtained through either intermolecular transformations, which are dominated by condensation reactions, [3][4][5][6][7] or intramolecular transformations, which include cross-coupling reactions [8][9][10] starting from ortho-haloaryl thioureas, and oxidative coupling reactions. [11][12][13][14][15] Herein, we present an iodobenzenepromoted Pd-catalysed synthesis of benzothiazoles via intramolecular coupling.…”
mentioning
confidence: 99%